(NwARIACII NA TEMU [OPENA sO^(B.22 (NwARIACII NA TEMU KORELLI(B. (NsO^(B.42s (NfORTEPIANOs - (Ns(B.(Nw(B.(NrAHMANINOWs ((NmOSKWAs (NlANXs, 2022)
(NwARIACII NA TEMU {OPENA bYLI SOZDANY W (B1903 (NGODUs
Keywords: (NFORTEPIANOs